Dominance solvability of dynamic bargaining games - Christopher J. Tyson (Queen Mary University of London, Department of Economics, 2009)
We formulate and study a general finite-horizon bargaining game with simultaneous moves and a disagreement outcome that need not be the worst possible result for the agents. Conditions are identified under which the game is dominance solvable in the sense that iterative deletion of weakly dominated strategies selects a unique outcome. Our analysis uses a backward induction procedure to pinpoint the latest moment at which a coalition can be found with both an incentive and the authority to force one of the available alternatives. Iterative dominance then implies that the alternative characterized in this way will be agreed upon at the outset - or, if a suitable coalition is never found, that no agreement will be reached.
Keywords: H41; D64; C62; 330; backward induction; coalition; core; weak dominance; Verhandlungstheorie; Koalition; Core; Theorie